Organelle Engineering in Yeast: Enhanced Production of Protopanaxadiol through Manipulation of Peroxisome Proliferation in Saccharomyces cerevisiae - Choi, Bo Hyun; Kang, Hyun Joon; Kim, Sun Chang; Lee, Pyung Cheon (Microorganisms, 2022)
Isoprenoids, which are natural compounds with diverse structures, possess several biological activities that are beneficial to humans. A major consideration in isoprenoid production in microbial hosts is that the accumulation of biosynthesized isoprenoid within intracellular membranes may impede balanced cell growth, which may consequently reduce the desired yield of the target isoprenoid. As a strategy to overcome this suggested limitation, we selected peroxisome membranes as depots for the additional storage of biosynthesized isoprenoids to facilitate increased isoprenoid production in Saccharomyces cerevisiae. To maximize the peroxisome membrane storage capacity of S.cerevisiae, the copy number and size of peroxisomes were increased through genetic engineering of the expression of three peroxisome biogenesis-related peroxins (Pex11p, Pex34p, and Atg36p). The genetically enlarged and high copied peroxisomes in S.cerevisiae were stably maintained under a bioreactor fermentation condition. The peroxisome-engineered S.cerevisiae strains were then utilized as host strains for metabolic engineering of heterologous protopanaxadiol pathway. The yields of protopanaxadiol from the engineered peroxisome strains were ca 78% higher than those of the parent strain, which strongly supports the rationale for harnessing the storage capacity of the peroxisome membrane to accommodate the biosynthesized compounds. Consequently, this study presents in-depth knowledge on peroxisome biogenesis engineering in S.cerevisiae and could serve as basic information for improvement in ginsenosides production and as a potential platform to be utilized for other isoprenoids.
Keywords: Ginsenosides; Isoprenoids; Peroxisome; Targeting